Taxonomic investigations of cyanobacterial and algal flora from the Southern Altai, East Kazakhstan - Caisová, Lenka; Bešta, Tomáš; Chlachula, Jiří; Komárek, Jiří; Husák, Štěpán (Biodiversity: Research and Conservation, 2010)
The study presents results of pilot investigations (2005-2007) of micro-vegetation biodiversity in marginally explored mountain and forest-steppe areas of southern Altai, East Kazakhstan. On the basis of morphological phenotypes and ecological demands a total of 351 taxa of cyanobacteria and algae were identified in the principal biotopes (rivers and streams, backwaters, irrigation channels, lakes, high-tundra periglacial and barren land settings, snow fields, and pedogenic /soil cover/environments) of the territorial topographic gradient of ca. 400-3900 m a.s.l. Microbiological records display a remarkable taxonomic variability, including several previously undescribed endemic species of algae adapted to locally specific geoenvironmental conditions. The present results show a major potential for future systematic phycological studies integrated in the complex nature monitoring and management strategy in protected areas of the Altai. The results also demonstrate a limited impact of modern human activity on the quality of local water sources with only minor present ecological risks in balance with the traditional lifestyles of pastoralist communities.